2010
DOI: 10.1123/jsr.19.3.288
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plyometric Training on Peroneal Latency

Abstract: Although latency measurements were consistent with previous studies, the plyometric training program did not cause significant change in the peroneus longus reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
6
18
2
Order By: Relevance
“…In this study, the mean peroneal latencies ranged from 88 to 102 msec and 86 to 91 msec in the non-dominant and dominant limbs, respectively. Although shorter peroneal reaction times (50-66 msec) in healthy ankles compared to our results were stated in a majority of the previous studies (10,28,31,32), the results of other studies (29,30) were quite comparable with our results. The mean anterior tibial latencies ranged from 95 to 105 msec and 90 to 101 msec in the non-dominant and dominant limbs, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, the mean peroneal latencies ranged from 88 to 102 msec and 86 to 91 msec in the non-dominant and dominant limbs, respectively. Although shorter peroneal reaction times (50-66 msec) in healthy ankles compared to our results were stated in a majority of the previous studies (10,28,31,32), the results of other studies (29,30) were quite comparable with our results. The mean anterior tibial latencies ranged from 95 to 105 msec and 90 to 101 msec in the non-dominant and dominant limbs, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The present study exhibited partially consistent results with the previous studies for reaction times for the peroneal and tibialis anterior muscles (10,(28)(29)(30)(31). In this study, the mean peroneal latencies ranged from 88 to 102 msec and 86 to 91 msec in the non-dominant and dominant limbs, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studies have examined a variety of interventions aimed to improve the reaction time (faster) of the peroneus longus in response to the ankle perturbation in an effort to decrease the likelihood of injury (Cordova et al, 2010;Han & Ricard, 2011;Henry et al, 2010;Ramanathan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consecutive ankle perturbations of three (Berg et al, 2007;Thain et al, 2015), five (Cordova et al, 2010;Henry 4 et al, 2010), six (Hopkins et al, 2006;Hopkins et al, 2007;Palmieri-Smith et al, 2009;Mitchell et al, 2008;Vaes et al, 2002), 10 (Han & Ricard, 2011Lynch et al, 1996) and 40 (Lynch et al, 1996) have been reported in the literature. The number of practice tilts is also selected heuristically, with some studies incorporating one practice trial before the main testing commences (Fernandes et al, 2000;Henry et al, 2010), others reporting 'several' trials (Berg et al, 2007;Hopkins et al, 2007), and others have no mention of practice at all (Ebig et al, 1997;Han & Ricard, 2011;Konradsen et al, 1997;Lynch et al, 1996;Mitchell et al, 2008;Palmieri-Smith et al, 2009). …”
Section: Introductionmentioning
confidence: 99%